(untitled) (Research, Society and Development, 2023)
The purpose was to carry out an educational intervention with medical students about diabetic foot care. This is an individual, longitudinal, interventionist and educational study. The students’ knowledge about the subject was analyzed through a questionnaire and the data obtained were shown in tables and graphs through descriptive and inferential statistical analysis, assuming the alpha level of significance < 0.05%. About 62% of the students were between 18 and 25 years old and 100% stated they never participate in any training program. Being observed evolution of knowledge through the questionnaires applied in the pre and post lectures, representing a better result after the training course. Health education in the context of diabetic foot syndrome can be applied as an essential instrument to offer quality care, given that educational practices can directly contribute to the knowledge of medical students and to the support of self-care for DM patient implementation.